DISCONTINUOUS MELT EXTRACTION AND WEAK REFERTILIZATION OF MANTLE PERIDOTITES AT THE VEMA LITHOSPHERIC SECTION (MID-ATLANTIC RIDGE) - Brunelli D.; Bonatti E.; Seyler M.; Cipriani A.; Ottolini L. (My University, 2006)
Melting processes beneath the Mid-Atlantic Ridge were studied in residual mantle peridotites sampled from a lithospheric section exposed near the Vema Fracture Zone at 11°N along the Mid-Atlantic Ridge. Fractional and dynamic melting models were tested based on clinopyroxene rare earth element and high field strength element data. Pure fractional melting (non-modal) cannot account for the observed trends, whereas dynamic melting with critical mass porosity <0·01 fits better the measured values. Observed microtextures suggest weak refertilization with 0·1-1% quasi-instantaneous or partially aggregated melts trapped during percolation. The composition of the melts is evaluated, together with their provenance, with respect to the garnet-spinel transition. Partial melts appear to be aggregated over short but variable intervals of the melting column. Deep melts (generated within the garnet stability field at the base of the melting column) escape detection, being separated from the residues by transport inside conduits or fractures. The temporal evolution of the melting process along the exposed section shows a steady increase of mantle temperature from 20 Ma to present. © 2006 Oxford University Press.
Keywords: ABYSSAL PERIDOTITE; MANTLE PARTIAL MELTING; REFERTILIZATION; TRACE ELEMENT; VEMA FRACTURE ZONE